2012
DOI: 10.21608/jappmu.2012.83317
|View full text |Cite
|
Sign up to set email alerts
|

Productive Performance, Some Rumen Parameters and Blood Profile of Zaraibi Goats Fed Rations Supplemented With Chufa Tubers During Late Preganncy and Suckling Periods.

Abstract: This research was conducted to evaluate effects of dietary supplement with Chufa tubers on the productive performance of Egyptian Zaraibi does and their newly born kids as well as some rumen parameters and blood profile. Twenty four pregnant does were divided into four equal groups (G1, G2, G3 and G4) and fed according to NRC (1981) allowances, where diets contained 0, 5, 10 and 15g Chufa tubers (CT)/h/d, respectively. The obtained results showed that the highest values of daily feed intake as % of BW and g/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…It may also be attributed to the higher requirements for milk production during early lactation period. Similar results were reported by Maged (2011) and Ahmed and El-Kholany (2012) and Mostafa et al (2014) with lactating cows and dairy goats during the late pregnancy and early lactation periods.…”
Section: Live Body Weightsupporting
confidence: 91%
“…It may also be attributed to the higher requirements for milk production during early lactation period. Similar results were reported by Maged (2011) and Ahmed and El-Kholany (2012) and Mostafa et al (2014) with lactating cows and dairy goats during the late pregnancy and early lactation periods.…”
Section: Live Body Weightsupporting
confidence: 91%
“…The LBW of does increased to the maximum before parturition and recorded the highest values (ranged from 44.30 to 47.10kg) then sharply decreased (post-parturition) to the minimum at day 90 th (weaning) in all groups (35.60 to 37.20kg). The same trend wasi observedlby Ahmed and El-Kholany (2012) with Zaraibi does during the late pregnancy and lactation periods. Devendra (1979) recorded a decline in body weight of high milk yielding goat during the first month post-partum.In another study on Zaraibi does duringlate pregnancy and lactation periods, Shehata et al (2007a) observed that the LBW of does increased to the maximum before parturition (end of pregnancy) and recorded the highest values (ranged from 55.7 to 58.8kg) then sharply decreased post-parturition to the minimum in suckling period .Similar results were observed also by El-Shinnawy et al (2010) with Rahmani ewes during the late pregnancy and suckling periods.…”
Section: Biochemical Parameterssupporting
confidence: 78%
“…Besides, CP concentrations tend to be higher in triticale, wheat, and barley than in oat silage. Moreover, using triticale silage and its mixture in ruminant rations had positive effects on digestion coefficients, feeding values, productive performance, and some metabolic parameters [14].…”
Section: Introductionmentioning
confidence: 98%